Success and Impact Factors of the Implementation of Electronic Medical Records in Hospitals; Literature Review - Uktuvia, Anik; Awanilah, Awanilah; Az-zahra, Elsha; Aditya, Muhamad Ilham; Sari, Nur Intan; Sabila, Sri Yunita (Journals of Ners Community, 2024)
The adoption of Electronic Medical Records (EMR) has become an essential step in strengthening healthcare services worldwide. EMR implementation contributes to improved efficiency, data accuracy, patient safety, and inter-unit coordination. In Indonesia, the Ministry of Health has mandated the digital transformation of medical records through Regulation No. 24 of 2022, which requires hospitals to migrate from paper-based systems to digital records. However, successful implementation depends largely on human resources (HR) readiness and technological support. This systematic literature review analyzed ten journal articles published between 2021–2025 to explore the success factors and impacts of EMR implementation in Indonesian hospitals. Findings reveal that HR factors, such as digital literacy, acceptance, and training, play a key role, while technology factors, such as system stability, internet connectivity, and vendor support, are equally crucial. The impacts include increased service efficiency, improved data quality, and higher user satisfaction, though challenges remain, including technical disruptions and staff resistance. Future research is needed to strengthen large-scale quantitative evidence and ensure sustainable integration of EMR into national health systems.